Interview with Maulana Mohammad Abbas Ansari and Mir Waiz Mohammad Omar Farookh of Jammu and Kashmir Liberation Front (JKLF). Interviewed by Kabir in Srinagar, 20/08/1999 - Kabir, Shahriar.
Interview with Maulana Mohammad Abbas Ansari and Mir Waiz Mohammad Omar Farookh of Jammu and Kashmir Liberation Front (JKLF). Interviewed by Kabir in Srinagar, 20/08/1999.